The jellyfish buffet: jellyfish enhance seabird foraging opportunities by concentrating prey - Sato, Nobuhiko N. (Biol Lett, 2015)
High levels of jellyfish biomass have been reported in marine ecosystems around the world, but understanding of their ecological role remains in its infancy. Jellyfish are generally thought to have indirect negative impacts on higher trophic-level predators, through changes in lower trophic pathways. However, high densities of jellyfish in the water column may affect the foraging behaviour of marine predators more directly, and the effects may not always be negative. Here, we present novel observations of a diving seabird, the thick-billed murre, feeding on fish aggregating among the long tentacles of large jellyfish, by using small video loggers attached to the birds. We show that the birds encountered large jellyfish, Chrysaora melanaster, during most of their dives, commonly fed on fish associated with jellyfish, and appeared to specifically target jellyfish with a high number of fish aggregating in their tentacles, suggesting the use of jellyfish may provide significant energetic benefits to foraging murres. We conclude that jellyfish provide feeding opportunities for diving seabirds by concentrating forage fish, and that the impacts of jellyfish on marine ecosystems are more complex than previously anticipated and may be beneficial to seabirds.